Prolonged Continuous Theta Burst Stimulation Can Regulate Sensitivity on Aβ Fibers: An Functional Near-Infrared Spectroscopy Study - Li, Chong; Zhang, Nannan; Han, Qiong; Zhang, Lifang; Xu, Shuo; Tu, Shuting; Xie, Yong; Wang, Zhiyong (Frontiers in Molecular Neuroscience, 2022)
Objective: High-frequency repetitive transcranial magnetic stimulation (rTMS) induces analgesic effects in both experimental pain and clinical pain conditions. However, whether rTMS can modulate sensory and pain thresholds on sensory fibers is still unclear. Here, we compared the effects of three rTMS paradigms on sensory and pain thresholds conducted by different sensory fibers (Aβ, Aδ, and C fibers) with sham stimulation and investigate the potential brain activation using functional near-infrared spectroscopy (fNIRS). Methods: Forty right-handed healthy subjects were randomly allocated into one of four groups. Each subject received one session rTMS (pcTBS, iTBS, 10 Hz rTMS or sham). Current Perception Threshold (CPT), Pain Tolerance Threshold (PTT), and fNIRS were measured at baseline, immediately after stimulation, and 1 hour after stimulation respectively. Results: Significant differences between treatments were observed for changes for CPT 2000 Hz between baseline and 1 hour after rTMS (F=6.551, P＜0.001): pcTBS versus sham (P=0.004) and pcTBS versus 10 Hz rTMS (P=0.007). There were significant difference in average HbO um in the right frontopolar cortex (FPC) (chanel 23: P= 0.030 (pcTBS versus sham: P=0.036)), left dorsolateral prefrontal cortex (DLPFC) (chanel 7: P=0.006 (pcTBS versus sham: P=0.004)), left FPC (chanel 17: P= 0.014 (pcTBS versus sham: P=0.046), chanel 22: P=0.004 (pcTBS versus sham: P=0.004)) comparing four group in 1 hour after stimulation in PTT 2000 Hz (Aβ-fiber). Conclusions: pcTBS can regulate sensitivity on Aβ fibers. In addition, single-session pcTBS placed on left M1 can increase the excitability of DLPFC and FPC, indicating the interaction between M1 and prefrontal cortex may be a potential mechanism of analgesic effect of rTMS. Studies in patients with central post-stroke pain are required to confirm the potential clinical applications of pcTBS.